1997
DOI: 10.1001/archneur.1997.00550160041013
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind Crossover Study With Physostigmine in Patients With Degenerative Cerebellar Diseases

Abstract: Treatment with physostigmine does not improve the conditions of patients with ataxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Most of these studies were negative or not conclusive due to limitations such as lack of randomization and of a placebo group, non-validated outcomes, multiple primary endpoints, inclusion of different types of cerebellar ataxia, and short periods of follow-up. Physostigmine [70], fluoxetine [71], tandospirone [72], lamotrigine [73], buspirone [74] and IGF-1 [75] are examples of the evaluated drugs with negative or non-conclusive results. None of these drugs can be recommended for the treatment of SCA3/MJD.…”
Section: Treatmentmentioning
confidence: 99%
“…Most of these studies were negative or not conclusive due to limitations such as lack of randomization and of a placebo group, non-validated outcomes, multiple primary endpoints, inclusion of different types of cerebellar ataxia, and short periods of follow-up. Physostigmine [70], fluoxetine [71], tandospirone [72], lamotrigine [73], buspirone [74] and IGF-1 [75] are examples of the evaluated drugs with negative or non-conclusive results. None of these drugs can be recommended for the treatment of SCA3/MJD.…”
Section: Treatmentmentioning
confidence: 99%
“…Adverse effects may limit treatment. Physostigmine has no significant effect on cerebellar tremor [162, 163]. …”
Section: Ataxia and Tremormentioning
confidence: 99%
“…The authors of both articles concluded that physostigmine was not effective in the treatment of this disease (13,53).…”
Section: Cortical Cerebellar Atrophiesmentioning
confidence: 99%
“…As previously mentioned, the results of trials with L-hydroxytryptophan (40,94), physostigmine (53), TRH (52), vigabatrin (91), riluzole (102) and buspirone (92), in groups that included patients with several types of ataxia, did not permit individualization of the effect of these drugs on FRDA.…”
Section: Spinocerebellar Atrophiesmentioning
confidence: 99%